USIA KEHAMILAN DAN PENGETAHUAN TENTANG HUBUNGAN SEKSUAL PADA MASA KEHAMILAN DENGAN SIKAP HUBUNGAN SEKSUAL SELAMA KEHAMILAN - NURMALIZA, LILI; SIHOMBING, JULIANA SION; LUBIS, NUR AZIZAH; LUBIS, RHINA CHAIRANI (LP2MTBM MAKARIOZ, 2024)
Sexual intercourse is a biological need carried out by husband and wife. Many couples are worried about having sex during pregnancy because they think it will harm the baby. In a normal pregnancy, the male genitals cannot make direct contact with the fetus because they are protected by the uterine muscle wall and amniotic fluid. There is a mucus plug around the cervix which will prevent sperm and bacteria from entering the uterus. The aim of the research is to determine the age of gestation and knowledge about sexual relations during pregnancy with attitude to sexual relations during pregnancy, The research results obtained were based on the good knowledge of 7 people with a good attitude of 6 people (20%) and a poor attitude of 1 person (3.33) and a poor knowledge of 23 people with a good attitude of 1 person (3.33) and a poor attitude of 22 people ( 76.66). with a value of 0.000, which means there is a relationship between knowledge and attitudes during sexual intercourse, It is hoped that the better a pregnant woman's knowledge about sexual relations, the better her attitude towards sexual relations during pregnancy will be